2019
DOI: 10.1101/679233
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cryo-EM structure of the complete and ligand-saturated insulin receptor ectodomain

Abstract: Glucose homeostasis and growth essentially depend on the peptide hormone insulin engaging its receptor. Despite biochemical and structural advances, a fundamental contradiction has persisted in the current understanding of insulin ligand-receptor interactions. While biochemistry predicts two distinct insulin binding sites, 1 and 2, recent structural analyses have only resolved site 1.Using a combined approach of cryo-EM and atomistic molecular dynamics simulation, we determined the structure of the entire dime… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 67 publications
1
27
1
Order By: Relevance
“…This indicates that studied insulin residues might not be involved in direct interactions with site 2 of receptors. Recently, two studies (42, 43) were published showing cryo-EM maps of the IR extracellular domains with insulin bound to a newly identified binding site that was proposed as a new site 2 and should interact with the insulin residues studied in this work. These new findings support the hypothesis of initial docking and transient interactions between insulin and IR.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This indicates that studied insulin residues might not be involved in direct interactions with site 2 of receptors. Recently, two studies (42, 43) were published showing cryo-EM maps of the IR extracellular domains with insulin bound to a newly identified binding site that was proposed as a new site 2 and should interact with the insulin residues studied in this work. These new findings support the hypothesis of initial docking and transient interactions between insulin and IR.…”
Section: Discussionmentioning
confidence: 92%
“…It is not excluded that future advances in X-ray crystallography or cryo-EM methodology will decipher structures of such hypothetical transient protein hormone complexes and reveal complex mechanisms of receptor activation by the hormones. In this context, during the preparation and revision of this manuscript, two studies (42, 43) were published showing cryo-EM maps of the IR extracellular domains with four insulins bound. Two of these insulins are positioned as shown previously by Scapin et al (21) but the binding site for the other two insulins is located in the FnIII-1 (or FnIII-1′) domain and was not detected previously.…”
Section: Discussionmentioning
confidence: 99%
“…During the revision of this manuscript, another study deposited in the preprint server bioRxiv also showed a low-resolution cryo-EM map of the IR extracellular domain with four insulins bound at sites 1 and 2 (Gutmann et al, 2019). The 3:1 or 4:1 stoichiometry of insulin binding to the IR dimer and the two types of binding sites are consistent with previous IR–insulin binding assays that indicated the coexistence of high- and low-affinity insulin-binding sites (Schäffer, 1994).…”
Section: Resultsmentioning
confidence: 99%
“…S1 ). A significant number of the residues that have been previously shown to be involved in insulin:IR or IGF-1:IGF1R interaction [ [28] , [29] , [30] , [31] , [32] , [33] ] are either conserved or conservatively substituted in dcVILPs ( Figure 1 A, Table 1 ). Structural studies have suggested that the mature IR or IGF1R can bind two insulin or IGF-1 molecules with high affinity, effectively crosslinking two binding subsites on IR/IGF1R named as Site 1 and Site 2 [ [28] , [29] , [30] , [34] , [35] , [36] ].…”
Section: Resultsmentioning
confidence: 99%